Peran Fear Of Missing Out Terhadap Kecanduan Media Sosial - Ditya Tri Amelia (Dinasti Review Publisher, 2023)
This research aims to examine the role of fear of missing out on social media addiction in early adulthood. This research uses quantitative methods. By taking samples using a purposive sampling technique. The subjects of this research were 150 individuals in early adulthood. The data were analyzed using simple regression analysis and the results showed that there was a significant role between fear of missing out on social media addiction in early adulthood at 51.1% with a sig value of 0.00 (p<0.05).